On the Measurement of Success and Satisfaction - René van den Brink; Frank Steffen (Tinbergen Institute, 2012)
The main purpose of the present paper is to disentangle the mix-up of the notions of success and satisfaction which is prevailing in the voting power literature. We demonstrate that both notions are conceptually distinct, and discuss their relationship and measurement. We show that satisfaction contains success as one component, and that both coincide under the canonical set-up of a simultaneous decision-making mechanism as it is predominant in the voting power literature. However, we provide two examples of sequential decision-making mechanisms in order to illustrate the difference between success and satisfaction. In the context of the discussion of both notions we also address their relationship to different types of luck.
urn:NBN:nl:ui:31-1871/38462
Keywords: C79; D02; D71; 330; success; satisfaction; luck; power; Abstimmungsregel; Macht; Zufriedenheit; Neue politische Ökonomie; Theorie